Effect of adding crude glycerine to diets with feed additives on the feed intake, ruminal degradability, volatile fatty acid concentrations and in vitro gas production of feedlot Nellore cattle - Almeida, Marco Tulio C.; Paschoaloto, Josimari R.; Perez, Henrique L.; Carvalho, Vanessa B.; Homem Junior, Antonio C.; Favaro, Vanessa R.; Blair, Hugh T.; Ezequiel, Jane M. B. (Wiley-Blackwell, 2019)
The effects of adding crude glycerine with sodium monensin or essential oils to beef cattle diets on the intake, degradability of DM and nutrients, rumen concentration of volatile fatty acids (VFA) and in vitro gas production were evaluated. Five ruminally cannulated Nellore steers were randomly assigned to a 5 x 5 Latin square design. The treatments were as follows: CONT, without crude glycerine and additives; EO, with essential oils and without crude glycerine; MON, with sodium monensin and without crude glycerine; EOG, with essential oils and crude glycerine; MONG, with sodium monensin and crude glycerine. Treatments with essential oil and sodium monensin increased the NDF and STC intake and the DM degradability. When crude glycerine was combined with either sodium monensin or essential oil, there was a reduction in DM, NDF and STC intake and an increase in DM and CP degradability of the diets. The adding crude glycerine to essential oil diets reduced the CH4 production. Sodium monensin treatments reduced DM and NDF intake and the production of total gas, CH4, total VFA and acetic acid concentration. In conclusion, the adding crude glycerine (200 g/kg DM) with either sodium monensin (0.03 g/kg DM) or essential oil (0.5 g/ kg DM) can be utilized in diets for Nellore cattle without causing detrimental effects on feed intake and improving the DM degradability.
Keywords: by-product; glycerol; growth promoters; Nellore